Anglo-Catholicism in West Wales: Lewis Gilbertson, Llangorwen And Elerch. (1st June 2020) - Chapman, Mark
Lewis Gilbertson (1815–1896) was one of the most prominent Anglo-Catholic clergy of St David's' diocese. He became the first incumbent of the new church at Llangorwen just outside Aberystwyth, built by Matthew Davies Williams, eldest brother of the Tractarian poet Isaac Williams (1802–65). Gilbertson adopted ritualist practices and Tractarian theology, which later influenced the church he was to build in Elerch (also known as Bont Goch) where his father, William Cobb Gilbertson (1768–1854), had built his house in 1818. After a brief survey of the development of Tractarianism in Wales, the paper discusses the building of the church at Llangorwen, which had the first stone altar since the Reformation in the Diocese of St David's, before discussing Gibertson's ministry in the parish. From Llangorwen Gilbertson moved to Jesus College, Oxford where he served as vice-principal and where he became increasingly convinced of the need for a new church and parish for his home village. He had earlier built a National School in 1856 commissioning the well-known Gothic revival architect G. E. Street. For St Peter's church, completed in 1868, he turned to William Butterfield, who had built the Tractarian model church of All Saints', Margaret Street in London. Gilbertson, who appointed himself as first incumbent for a brief period, set the ritualist tone of the parish while at the same time ensuring regular Welsh-language services to attract villagers from what he called the 'broken shadow of practices of the primitive Church' of the Welsh Methodists. The paper concludes with a brief discussion of Gilbertson's later career before assessing the impact of Tractarianism in west Wales, especially the confident and idealistic vision of a return to the apostolic faith for all the people of Wales on which it was established.